Avaliação de sandálias impregnadas com repelente espacial e o seu efeito na biologia e proteção contra picadas do mosquito Aedes aegypti (diptera: culicidae) - Tales Batista Ribeiro (2022)
The search for new technologies to prevent arboviruses transmitted by Aedes aegypti has received attention in recent decades due to unsatisfactory results fromconventional control methods. Recently, there has been an increase in studies using spatial repellents, which prevent human-vector contact and create a mosquito-free area, resulting in protection against bites and reducing disease transmission. The present workaimed to develop and evaluate transfluthrin as a space repellent and its effect on biologyand protection against Ae. aegypti under laboratory and semi-field conditions. The effectof transfluthrin (2% and 8%) impregnated in hessian strips on the behavior and biology of Ae. aegypti was evaluated in semi-field laboratory bioassays. In the laboratory, (i) exposure of caged mosquitoes screened for 30 min. at 50 and 100 cm of distance to a fan,making a air flow induced a greater knock down effect compared to mortality, regardless of distance; (ii) in double-choice olfactometer, both transfluthrin concentrations inhibitedattraction towards human odor and induced >60% mortality rate in mosquitoes and (iii) in repellence boxes (BG-Cages) using forearms of volunteers, we demonstrated that both concentrations reduced the attempt to bite the volunteers and that the concentration of 8%offered greater protection (49.05%). In semi-field, (i) mosquitoes were exposed to a volunteer wearing prototype sandals impregnated with transfluthrin (8%) with different hessian surface areas (10, 20, 40, 80 and 160 cm²). It was observed that the greatest protection (45.5%) against bites occurs with the sandal with the greatest area of release. (ii) A pair of impregnated sandals with an area of 327cm² were placed on the ground andscreened pots containing 25 females of Ae. aegypti was placed at different distances andheights for 30 min and then mortality up to 24 h, knock down (1 h after the end of exposure) and blood meal after exposure were verified. Knock down effect and mortalitywere observed in all combinations of heights and distances from the transfluthrin source,however the inhibition of hematophagy was observed only in mosquitoes positioned at 1m in height and at 1.4 m and 7.0 m away from the impregnated sandals. (iii) Volunteers wearing sandals impregnated (160 cm²) with different concentrations of transfluthrin (2,5, 8, 10 and 15%) had protection from stings at all concentrations, but the greatest protection (51.5%) occurred at the concentration of 2%. The transfluthrin impregnated inhessian strips caused changes in the biology of Ae. aegypti in laboratory and semi-field bioassays and was effective in protecting against bites, demonstrating the potential of this technology to complement current control methods